THE BṚHAD BHAGAVATĀMṚTA AND SANĀTANA GOSVĀMIN: A GREAT VAISNAVA SCHOLAR OF BENGAL - Dipankar Karmakar (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Vaiṣṇavism as a religious cult, was not very new in Bengal. It existed in some form or other long before the advent of Śri Caitanya. It was current in Bengal in medieval times and was patronized by the Vaiṣṇavite Brahmans of East Bengal and Lakshman Sen. Sri Sanātana Gosvāmin, a direct disciple of Sri Caitanya and one of the six founders of Bengal Vaisnavism. He enriched Vaisnavism with his luminous thoughts and provided it with an abiding social foundation through his own holy life. Caitanyaism, as it is known today, is principally the creation of Sanatana, Rūpa, Jiva and their disciple Kṛṣṇadāsa Kaviraja. Sanātana was principally an ascetic devotee, his contribution to the interpretation of scriptures and the formulation of Vaisnava theology is of primary importance. Sanātana was undoubtedly a man of profound scholarship and great literary talents and a spiritually illumined soul who, through his life-long labour, enriched Vaiṣṇava devotional literature and laid the theological foundation of the sect. Who is the original Bhakta? and what is Bhakti? These things are elaborated in a very spiritual way in Sanātana's Bṛhad-Bhagavatamṛta. This paper illuminates the thoughts of Sanātana and his work Bṛhad-Bhagavatamṛta.